Cooperative governance under increasing member diversity: Towards a new theoretical framework. Issue 1 (March 2022) - Iliopoulos, Constantine; Valentinov, Vladislav
Highlights: Cooperative governance is about choosing core activities. Inflation of peripheral activities entails unmanageable governance costs. Member preference diversity may cause intra-cooperative frictions. Addressing the root causes of member preference diversity increases longevity. Drawing clear boundaries between core and periphery is a key governance task. Abstract: In advancing the notion of stakeholder capitalism, the great reset of management and organization theory must address governance implications of stakeholder heterogeneity. The paper contributes to this task by focusing on the governance of agricultural cooperatives whose members often have heterogeneous preferences. The key novel idea is to conceptualize cooperative governance in the light of the proposed distinction between the core and peripheral activities of cooperatives. While core activities are based on members' truly common interests, peripheral activities include all else. This approach allows tracing governance challenges of agricultural cooperatives back to the inflation of peripheral activities. Based on this approach, cooperative managers and members are advised to minimize these activities and to draw clear boundaries between core and periphery.